Comparative efficacy and safety of symptomatic therapy and disease-modifying therapy for Alzheimer’s disease: a systematic review and network meta-analysis - Liu, Shiyu; Zhao, Min; Liu, Yuan; Yang, Xin; Yan, Huayu; Xu, Hongcai; Wu, Yabo; Xu, Yumin (Frontiers in Neuroscience, 2025)
BackgroundThe management of Alzheimer’s disease has shifted toward disease-modifying therapies aimed at delaying disease progression rather than focusing solely on symptomatic treatment. This study summarizes the latest evidence regarding the benefits and harms of anti-Alzheimer’s disease drugs.MethodsWe conducted a comprehensive review of randomized controlled trials from PubMed, Embase, Cochrane Library, Web of Science databases, and other sources up to April 2025. Two researchers independently reviewed the literature and analyzed the data. A network meta-analysis was performed using Review Manager version 5.3 and Stata version 18.0 to calculate mean differences (MDs) and 95% confidence intervals (CIs) for direct and indirect comparisons. Treatment efficacy was evaluated using the Surface Under the Cumulative Ranking Curve (SUCRA). Bias was assessed using the Revised Cochrane Risk of Bias Tool version 2.0, and publication bias was analyzed with funnel plots.ResultsThe network meta-analysis included 23 randomized controlled trials with 16,010 participants, evaluating nine pharmacological interventions ranging from traditional symptomatic therapies to four United States Food and Drug Administration- and National Medical Products Administration-approved disease-modifying therapies, notably anti-amyloid beta monoclonal antibodies. Aducanumab significantly improved ADAS-cog scores compared with placebo (MD -5.97, 95%CI -10.33, −1.61; SUCRA: 93.0%) and demonstrated notable improvements in ADCS-ADL scores (MD 4.99, 95%CI 2.27, 7.72; SUCRA: 98.6%). Memantine ranked highest for neuropsychiatric symptoms (SUCRA: 80.8%). Aducanumab also had the highest SUCRA for CDR-SB (91.5%) and showed moderate superiority in MMSE scores (MD 3.55, 95%CI 1.35, 5.75; SUCRA: 98.2%).ConclusionSymptomatic treatments, especially memantine for neuropsychiatric symptoms, remain effective. However, the network meta-analysis indicates that, for patients with mild cognitive impairment or mild Alzheimer’s disease, aducanumab demonstrates the greatest potential for cognitive and clinical improvement (MMSE, ADAS-cog, ADCS-ADL), despite associated risks such as adverse events and amyloid-related imaging abnormalities linked to disease-modifying therapies. Lecanemab provides moderate benefits, while donanemab appears less effective. Thus, clinicians should apply disease-modifying therapies cautiously and individually, carefully balancing potential risks and benefits for each patient.Systematic review registrationPROSPERO [CRD42025637730], https://www.crd.york.ac.uk/PROSPERO/.